NOSOLOGIC VARIANTS OF GLUTEN INTOLERANCE - T.E. Lavrova (Union of pediatricians of Russia, 2006)
The article reviews the problem of gluten intolerance, that is associated with gluten sensitive entheropathy (gee heuner herter or celiac disease) and food (wheat) allergic reactions. Defilement treatment approaches demand proper nosological diagnostic - celiac disease requires strict life time gluten free diet while wheat allergy would stand for temporary gluten free diet. The article elucidates the importance of proper diagnostics in acute period with morphological verification of the diagnosis and reveals pros and cons of serologic methods.Key words: gluten intolerance, gee heubner herter (celiac) disease, gluten sensitive entheropathy, food allergy, children.